IOP Conference Series: Earth and Environmental Science - Maruschak; Bishchak; Maruschak; Panin specialist in the field of material science Professor of Tomsk Polytechnic University, Doctor of technical sciences (2018)
The authors investigated the main regularities in the structural and mechanical degradation of steel and a welded joint of the "Soyuz" gas main in operation. It is established that the defect accumulation kinetics in welds are determined both by technological disruptions in their manufacture and by hydrogenation of the weld during a long operating time. A weakening of the mechanical properties of the weld after a prolonged operation is shown, which in some cases led to the appearance of cracks and fracture of the gas main.